A rapid point-of-care population-scale dipstick assay to identify and differentiate SARS-CoV-2 variants in COVID-19-positive patients - Paul, Deepjyoti; Verma, Jyoti; Kumar, Shakti; Talukdar, Daizee; Jana, Pradipta; Narendrakumar, Lekshmi; Kumar, Roshan; Tanwar, Subhash; Gosain, Mudita; Porey Karmakar, Sonali; Pareek, Madhu; Mani, Shailendra; et al. (Frontiers in Microbiology, 2024)
Delta and Omicron variants of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) are remarkably contagious, and have been recognized as variants of concern (VOC). The acquisition of spontaneous substitutions or insertion–deletion mutations (indels) in the spike protein-encoding gene substantially increases the binding affinity of the receptor binding domain (RBD)-hACE2 complex and upsurges the transmission of both variants. In this study, we analyzed thousands of genome sequences from 30 distinct SARS-CoV-2 variants, focusing on the unique nucleic acid signatures in the spike gene specific to the Delta and Omicron variants. Using these variant-specific sequences, we synthesized a range of oligonucleotides and optimized a multiplex PCR (mPCR) assay capable of accurately identifying and differentiating between the Delta and Omicron variants. Building on this mPCR assay, we developed a dipstick format by incorporating a tag linker sequence at the 5′ end of the forward primer and adding biotin to the 3′ end of the oligonucleotides, enhancing the assay’s usability and accessibility. Streptavidin-coated latex beads and the dipstick imprinted with a probe for the tag linker sequence in the test strips were used for the detection assay. Our dipstick-based assay, developed as a rapid point-of-care test for identifying and differentiating SARS-CoV-2 variants has the potential to be used in low-resource settings and scaled up to the population level.